Monday

December 22, 2014

December 22, 2014

Posted by **JAYZ** on Saturday, January 25, 2014 at 6:38pm.

- Calculus 1 -
**bobpursley**, Saturday, January 25, 2014 at 6:43pmput for y, 3x into the equation.

3x^2-x*3x + 9x^2=64

9x^2=64

x= +- sqrt (64/9) you can reduce this

and y is +-3sqrt (64/9) you can reduce this.

**Answer this Question**

**Related Questions**

Algebra 2 - 1. Give 3 points that lie on the line 4x-y=6. 2. Give 3 points that ...

Algebra 2 - 1. Give 3 points that lie on the line 4x-y=6. 2. Give 3 points that ...

Algebra 2 - 1. Give 3 points that lie on the line 4x-y=6. 2. Give 3 points that ...

calculus - use implcit differenciation to find an eqaution of both the tangent ...

Math - Rewrite the following definition as a biconditional: Points that lie on ...

Calculus - The line that is normal to the curve x^2=2xy-3y^2=0 at(1,1) ...

Calculus (pleas help!) - Find the slope of the tangent line to the ellipse x^2/...

calculus - The ellipse x^2+3y^3=13, has two points when x+-1 . Find the slope of...

Math - Use the distance formula to determine whether the points lie on the same ...

calculus - 1. Consider the function f(x) = X^(4/3) +4x^(1/3) on the interval -8...